(untitled) (Jalalabad Medical Journal, 2025)
Pneumonia-associated mortality is the leading cause of fatalities in children under 5 years of age. Breast milk provides adequate nutrition and immunity to children against harmful bacteria, thus protecting them from infections like pneumonia. Despite several beneficial effects of breastfeeding, mothers in many countries, even industrialised countries, are incurious about breastfeeding their infants and children, leading them to severe life-threatening diseases like pneumonia. This case-control study was conducted from January 2018 to July 2018 in the Department of Paediatrics, Jalalabad Ragib-Rabeya Medical College Hospital to evaluate the effect of breastfeeding on pneumonia in 6 to 24 months old children. A total of 200 children were included in this study by purposive sampling. Study subjects were divided into two groups. A hundred children who were suffering from pneumonia were included in group I and considered as cases. Group II, which was deemed the control group, contained 100 children who showed no symptoms of pneumonia. Data was collected from the parents of children in a structured questionnaire. The data was analyzed using SPSS version 22. Children who were not under exclusive breastfeeding were more prone to develop pneumonia (p<0.05). But the duration of breastfeeding had no significant effect on the development of pneumonia in our study (p>0.05). Practices that promote breastfeeding are an essential way to lower the incidence of pneumonia. Jalalabad Med J 2022; 19 (1): 21-26